2020
DOI: 10.1097/md.0000000000021967
|View full text |Cite
|
Sign up to set email alerts
|

Drone for medical products transportation in maternal healthcare

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…DBD can be used as a rapid delivery mechanism in emergency situations, such as maternal haemorrhage, delivering blood from a satellite bank to the site in need, or as an alternative blood banking system for managing storage and distribution of blood products. 13 This model has already been used to deliver blood and other medications in many countries, both HICs (USA and Switzerland) and LMICs (Rwanda, Haiti, the Dominican Republic, and Guinea). 14 …”
Section: Resultsmentioning
confidence: 99%
“…DBD can be used as a rapid delivery mechanism in emergency situations, such as maternal haemorrhage, delivering blood from a satellite bank to the site in need, or as an alternative blood banking system for managing storage and distribution of blood products. 13 This model has already been used to deliver blood and other medications in many countries, both HICs (USA and Switzerland) and LMICs (Rwanda, Haiti, the Dominican Republic, and Guinea). 14 …”
Section: Resultsmentioning
confidence: 99%
“…Drones have proven to be an effective tool for delivering these supplies to disaster sites, ensuring their timely arrival and alleviating the burden on rescue workers [64]. By facilitating the transportation of food, medical supplies, and other emergency resources, drones play a vital role in providing relief assistance in the maritime sector [65].…”
Section: Delivery Of Relief Suppliesmentioning
confidence: 99%
“…Although the results of the first few studies on this topic were promising, they also revealed some problems with transport conditions, and the costs were still higher than transportation using ground vehicles. 16,17 In conclusion, before implementing home sampling, the transport times of DBS cards to the laboratory should be known. The exact transport time is usually a black box and can only be established by test-sending envelopes.…”
Section: Distribution and Transportmentioning
confidence: 99%